2020
DOI: 10.1136/vr.105686
|View full text |Cite
|
Sign up to set email alerts
|

Paralytic shellfish poisoning and palytoxin poisoning in dogs

Abstract: BackgroundFatal cases of exposure to paralytic shellfish toxins and palytoxins have occurred in companion animals but are poorly described.MethodsWe describe one case of paralytic shellfish poisoning (PSP) and three cases of palytoxin poisoning in dogs.ResultsMild PSP occurred following ingestion of crab while walking on a beach. Analysis confirmed the presence of paralytic shellfish toxins, particularly decarbamoyl saxitoxin, in clinical samples and marine organisms. This case occurred shortly after an outbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Between 2017 and 2018, in England, there were multiple incidents of illness in dogs reported, due to the consumption of marine animals. The dogs were reported to have eaten different beached marine animals, such as crabs, starfish, and dab fish that led to different negative effects, such as vomiting, loss of motor control, muscle paralysis, and in some cases death [ 13 , 87 ]. Subsequential analyses found that the crabs, starfish, and dab fish from the beaches presented high concentrations of PSTs, with concentrations 18 times higher than those permitted by the European Union (i.e., over 14,000 µg STX eq/kg found in one starfish sample) [ 13 ].…”
Section: Toxic and Venomous Species Involved In Domestic Animal Poiso...mentioning
confidence: 99%
See 4 more Smart Citations
“…Between 2017 and 2018, in England, there were multiple incidents of illness in dogs reported, due to the consumption of marine animals. The dogs were reported to have eaten different beached marine animals, such as crabs, starfish, and dab fish that led to different negative effects, such as vomiting, loss of motor control, muscle paralysis, and in some cases death [ 13 , 87 ]. Subsequential analyses found that the crabs, starfish, and dab fish from the beaches presented high concentrations of PSTs, with concentrations 18 times higher than those permitted by the European Union (i.e., over 14,000 µg STX eq/kg found in one starfish sample) [ 13 ].…”
Section: Toxic and Venomous Species Involved In Domestic Animal Poiso...mentioning
confidence: 99%
“…The dogs were reported to have eaten different beached marine animals, such as crabs, starfish, and dab fish that led to different negative effects, such as vomiting, loss of motor control, muscle paralysis, and in some cases death [ 13 , 87 ]. Subsequential analyses found that the crabs, starfish, and dab fish from the beaches presented high concentrations of PSTs, with concentrations 18 times higher than those permitted by the European Union (i.e., over 14,000 µg STX eq/kg found in one starfish sample) [ 13 ]. Overall, Turner and coworkers, using LC-FLD analysis, reported that the PSTs present in beach samples were three analogues: dicarbamoyl saxitoxin (dsSTX), saxitoxin (STX), and gonyautotoxins 5 (GTX5) [ 87 ].…”
Section: Toxic and Venomous Species Involved In Domestic Animal Poiso...mentioning
confidence: 99%
See 3 more Smart Citations